Analysis of the phenomenon of over-the-counter drug abuse and not controlled herbs trade by polish adolescents: Part I - Daria Suchecka; Jolanta Kucharska-Mazur; Katarzyna Groszewska; Monika Mak; Jerzy Samochowiec; Agnieszka Samochowiec (Nofer Institute of Occupational Medicine, 2017)
The phenomenon of stupefying by the use of available over-the-counter drugs (OTC) among adolescents is an essential problem in both Poland and throughout the world. Popular analgesics, cold medicine and antihistamines contain psychedelic substances, such as dextromethorphan (DXM), pseudoephedrine/ephedrine, codeine (methylmorphine), dimenhydrinate, paracetamol (acetaminophren) and others. Cases of fatal addiction to dextromethorphan, one of the active substances contained in medicines, e.g., the common cold, have been reported. The test results cited by the authors clearly indicate that the use of OTC drugs, whose turnover is not controlled is a domain of females. The extent of use of drugs not prescribed by a doctor has remained for many years at a constant level. The most common poisonings with OTC drugs are caused by those that affect the respiratory system or exert analgesic or antipyretic effects. They are also used in attempted suicides, especially among females. Analyzing poisonings caused by OTC medications their seasonality has been observed. Their number increases during spring-autumn. A territorial differentiation in areas of OTC drug trade in terms of their quantities, with the predominance of southern regions is also noted. Intoxication with psychoactive substances causes the deterioration of relations between young people. In the reviewed studies there is no detailed information on the composition of non-prescription medicines. Moreover, young people have easy access to mushroom fungi, growing in nearby forests and meadows that may have hallucinogenic effects and are available in pharmacies and on the Internet. Med Pr 2017;68(3):413-422